2010
DOI: 10.1042/an20100019
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Neuroplasticity

Abstract: The production of neurons from neural progenitor cells, the growth of axons and dendrites and the formation and reorganization of synapses are examples of neuroplasticity. These processes are regulated by cell-autonomous and intercellular (paracrine and endocrine) programs that mediate responses of neural cells to environmental input. Mitochondria are highly mobile and move within and between subcellular compartments involved in neuroplasticity (synaptic terminals, dendrites, cell body and the axon). By genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
267
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(275 citation statements)
references
References 158 publications
2
267
0
6
Order By: Relevance
“…S4B and Table S1). Mitochondrial respiratory function is essential for neural processing, as it plays key roles in many essential functions required for neural homeostasis and computations (24)(25)(26). Thus, we reasoned that the disadvantage of high-anxious rats to win the competition against lowanxious rats could reflect a lower mitochondrial activity in the NAc.…”
Section: Significancementioning
confidence: 99%
“…S4B and Table S1). Mitochondrial respiratory function is essential for neural processing, as it plays key roles in many essential functions required for neural homeostasis and computations (24)(25)(26). Thus, we reasoned that the disadvantage of high-anxious rats to win the competition against lowanxious rats could reflect a lower mitochondrial activity in the NAc.…”
Section: Significancementioning
confidence: 99%
“…It has been reported that a single neuron in the human brain can consume~4.7 billion ATP molecules per second (Nicholls and Budd, 2000). Therefore, a continuous source of mitochondrial ATP is essential for neuronal function and synaptic plasticity (Cheng et al, 2010). As described as a component of the normal biology for KE3, the mitochondria is directly involved in supplying ATP to AC for conversion to cAMP, which acts as a second messenger involved in the signaling pathway leading to CREB/CRE activation (Fig.…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
“…These changes may include mitochondrial Ca 2+ uptake or release, production of superoxide and other ROS, and release of proteins and other factors. 13 …”
Section: Mitochondria: the Crucial Signalingmentioning
confidence: 99%
“…[11][12][13] Several prominent signaling pathways that stimulate mitochondrial biogenesis and energy metabolism, while simultaneously regulating neuroplasticity, have been demonstrated. 13 Mitochondria are distributed throughout the length of axons and presynaptic terminals. In addition, they are found in dendrite shafts and associated with dendritic spines.…”
Section: Mitochondria: the Crucial Signalingmentioning
confidence: 99%
See 1 more Smart Citation